Incidencia del materialismo dialéctico en la consolidación de la pedagogía crítica del siglo XXI. - De la Cruz Tapia, David Eliecer (2016)
We analized the influence of dialectic materialism in the development of critic Pedadogy in the 21 st century, Based in bibliographic and documental methods, our research analyzes the basis of Marx and Engels theory about dialectical materialism wich constitutes marxism theory itself. Then, our research includes Critic Pedagogy postulates and its historical development. We included Freire, Giroux, and McLaren's postulates too. These two investigations let us identify the influence of Dialectic Materialism in the consolidation of Critic Pedagogy in the 21st century. We identified too its limitations in educational matters. Through our research we found the way Dialectical materialism constitutes the leading theorical support for Critic Pedagogy, because of its transforming hermeneutic basis that lead Pedagogy touch the real world to educate and transform it at the same time.